Analysis of Report Generation of Daily Production in Manufacturing Industry using IoT - Sewatkar, Mayuri; Khachane, Ajitkumar (International Journal of Computer Sciences and Engineering, 2019)
Immediately IoT or Internet of things is a technology that deals with bringing control of physical devices over the Internet. Here I propose an efficient industry automation system that allows the user to efficiently fetch data from physical machines over the Internet. My system will analyze that particular data and determine the exact loss or profit of the company. For a demonstration of this system, I'm using 2 loads (temperature and count) as industrial appliances like temperature and counter. My main system takes the information and passes it to the Internet for further processing. The sensors and a microcontroller will be used for sending data from machine to system. Also, it displays the system state on an LCD display. Thus, we can automate the entire industry using online GUI for easy industry automation.